2021
DOI: 10.1037/emo0000672
|View full text |Cite
|
Sign up to set email alerts
|

Age and emotion regulation in daily life: Frequency, strategies, tactics, and effectiveness.

Abstract: Models of aging and emotion hypothesize age differences in emotion regulation-in frequency, use of strategies, and/or effectiveness-but research to date has been mixed. In the current experience sampling study, younger, middle-aged, and older adults (N ϭ 149), were prompted 5 times a day for 10 days to report on both general strategies (e.g., situation selection, cognitive change) and specific tactics. For each of the 5 strategies proposed by Gross's process model, tactics included those that introduced/increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 62 publications
(110 reference statements)
5
62
0
1
Order By: Relevance
“…Although across the sample, people tended to share with close (vs. non-close) others and seek emotion-oriented goals only relative to problemoriented goals only, these tendencies decreased with increasing age. These unexpected findings may be because we examined IER after negative events have occurred, as predictions based on the socioemotional selectivity theory have been supported for ER efforts that occur early in the emotion-eliciting process (e.g., situation selection; Livingstone & Isaacowitz, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Although across the sample, people tended to share with close (vs. non-close) others and seek emotion-oriented goals only relative to problemoriented goals only, these tendencies decreased with increasing age. These unexpected findings may be because we examined IER after negative events have occurred, as predictions based on the socioemotional selectivity theory have been supported for ER efforts that occur early in the emotion-eliciting process (e.g., situation selection; Livingstone & Isaacowitz, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…However, there is mixed evidence to support the idea that older adults are better able to modulate their emotions (Allen & Windsor, 2019). Experience sampling work suggests that older adults are more likely to meet their emotional goals in daily life (Scheibe et al., 2013), although there are not age differences in the effectiveness of specific strategies (Livingstone & Isaacowitz, 2021). An experiment that manipulated strategy use found that older adults were better able to modulate their emotions than younger adults when using positive reappraisal but less effective with detached reappraisal and similarly effective with suppression (Shiota & Levenson, 2009).…”
Section: Empirical Evidence Regarding Age‐related Shifts In Ermentioning
confidence: 99%
“…Age differences in the use of various ER strategies may also depend on the specific emotion being regulated, as there were not age differences in habitual reports of suppression use specifically with anger (Phillips et al., 2006). Finally, recent ecological momentary assessment work tracking ER across daily life finds age similarity in the use of a wide range of strategies (Eldesouky & English, 2018; Livingstone & Isaacowitz, 2021).…”
Section: Empirical Evidence Regarding Age‐related Shifts In Ermentioning
confidence: 99%
“…Further, prior work has shown that older adults actually prefer being sampled via electronic devices, relative to filling out pen and paper questionnaires (Gwaltney et al, 2008). Moreover, EMA studies have reported higher rates of compliance in older, relative to younger adults (e.g., Livingstone & Isaacowitz, 2019). Despite EMA bringing in its own methodological challenges and complications, it is our view that the benefits often far outweigh the costs, making EMA a promising and integral component of the methodological toolbox researchers can use to study aging across a wide variety of domains.…”
Section: Aging and Ecological Momentary Assessmentmentioning
confidence: 99%